HiWinGS BVOC Concentrations and Flux - Bertram, Timothy (Wiley, 2017)
The data set described here contains simultaneous, underway eddy covariance measurements of the vertical flux of isoprene, total monoterpenes, and dimethyl sulfide (DMS) over the Northern Atlantic Ocean during fall.
Keywords: Atmospheric Chemistry; Eddy Covariance Fluxes; Volatile Organic Compounds (VOC); High Wind Gas Exchange Study (HiWinGS); Air-Sea Gas Exchange